Acene‐Modified Small‐Molecule Donors for Organic Photovoltaics. Issue 53 (20th August 2019) - Sung, Min Jae; Hong, Jisu; Cha, Hyojung; Jiang, Yifei; Park, Chan Eon; Durrant, James R.; An, Tae Kyu; Kwon, Soon‐Ki; Kim, Yun‐Hi
Abstract: A series of acene‐modified small molecules have been designed and synthesized, and their photovoltaic characteristics were studied by using the small molecules in organic photovoltaics (OPVs). Different cores were introduced to modulate the conjugation lengths of the small molecules and the bulk heterojunction (BHJ) morphologies. Three small‐molecule donors were prepared, namely Ph‐TTR, Na‐TTR, and An‐TTR, which have phenyl, naphthalene, and anthracene moieties, respectively, as conjugated cores. These donors were synthesized in a few steps and exhibited favorable BHJ morphologies, thereby giving promising power conversion efficiencies (PCEs). The donors showed excellent miscibility with the acceptor PC71 BM, and the use of the additive 1, 8‐diiodooctane (DIO) led to a remarkable increase in crystallinity, thereby increasing the PCEs of their OPVs. Of the three donors, Na‐TTR showed the most efficient charge carrier generation and favorable molecular packing structures; hence, of the three types of devices tested, the Na‐TTR:PC71 BM devices exhibited the highest PCE, specifically 6.27 %, without pre‐ or post‐treatments. The promising PCEs achieved from these easily synthesized acene‐modified small molecules suggested that acene‐modified small molecules can be useful materials in OPVs. Abstract : Power conversion efficiencies : The morphologies and charge carrier dynamics of organic photovoltaics that incorporate new acene‐modified small molecules are studied (see picture; PCBM=[6, 6]‐phenyl‐C61 ‐butyric acid methyl ester, PEDOT:PSS=poly(3, 4‐ethylenedioxythiophene)polystyrene sulfonate, ITO=indium tin oxide).